Respons Pertumbuhan dan Produksi Kacang Tanah (Arachis hypogaea L.) dengan Pemberian Pupuk Kandang Ayam dan Pupuk NPK (15:15:15) - William Josua Damanik; Rosita Sipayung; Haryati Haryati (Universitas Sumatera Utara, 2015)
For the last six years in a row, the yield of peanut in Indonesia had encountered the decreasingyield problem. In case of that, the using chicken manure as organic material and NPK (15:15:15)fertilizer were aimed to increase growth and yield of peanut. The research has been conducted at theexperimental fields of Agriculture Faculty, Universitas Sumatera Utara, Medan from October 2013until February 2014. This research used factorial randomized block design with two factors, i.e.doses of chicken manure (0; 25; 50; 75 g/polybag) and doses of NPK (15:15:15) fertilizer (0; 0,625;1,25; 1,875 g/polybag). Parameters observed were number of branches, flowering age, gynophoresformed, pods per sample, pods per plot, seed weight per sample, dry weight of 100 seeds, freshweight of biomass, and dry weight of biomass. The results showed that the treatment of usingchicken manure significantly influenced the parameters of branches, gynophores formed persample, pods per sample, pods per plot, seed weight per sample, wet weight biomass per sample anddry weight biomass per sample. The treatment of NPK (15:15:15) significantly influenced theflowering age and dry weight of 100 seeds. The interaction between the both of treatmentsignificantly influenced dry weight of 100 seeds.Keywords : peanut, chicken manure, NPK (15:15:15) fertilizer